Translation Strategies Found In Translating Script Of Dramapada Suatu Hari Into Silly Jealousy - Sari, Heppy Ratno; , Dr. Dwi Haryanti, M.Hum; , Nur Hidayat, M.Pd (2014)
The purposes of this research are to explain type of strategies used, to identify dominant types of strategies used and to explain the equivalence of translation in Pada Suatu Hari into Silly Jealousy. The type of this research is descriptive qualitative. The data of this research is translation text in Pada Suatu hari into Silly Jealousy. The researcher uses documentation to collect the data. The researcher also uses comparative method to analyze the data of this research. The result of this research shows that there are 979 data that found by the researcher. First, there are thirteen types of strategies uses, they are 160 data or 16% include addition of word, 55 data or 6% include addition of phrase, 63 data or 6% include addition of clause, 30 data or 3% include addition of sentence, 143 data or 15% include deletion of word, 60 data or 6% include deletion of phrase, 51 data or 5% include deletion of clause, 26 data or 3% deletion of sentence, 130 data or 13 % include adoption, 86 data or 9% include level shift, 39 data or 4% include structural shift, 105 data or 11% include class shift and 31 data or 3% include intra system shift. Second, dominant type of strategies used that found by researcher is addition of word. Third, the researcher finds 361 data or 37% include equivalence of translation and 619 data or 63% include non-equivalence of translation.